2022
DOI: 10.1038/s41598-022-04968-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the interaction between BMI and dyslipidemia on hypertension in adults

Abstract: Body mass index (BMI) and dyslipidemia are indicators of human health and are often associated with high blood pressure. In this study,we explored the relationship between BMI or dyslipidemia and the risk of hypertension and further verified the possible interacting influences of BMI with dyslipidemia on the risk of hypertension. The aim is to explore the possible risk factors of hypertension and to provide scientific basis for the prevention and treatment of hypertension. Eligible subjects were selected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 28 publications
6
42
1
4
Order By: Relevance
“…Furthermore, older adults in this study with increased BMI had higher odds of being diagnosed with hypertension and diabetes. Consistent with the current findings, past research established that low body weight is an independent protective factor for hypertension ( Tang et al, 2022 ), whereas overweight/obesity are risk factors for hypertension and diabetes ( Chen et al, 2018 ; Medhi et al, 2021 ; Min & Cho, 2018 ; Tang et al, 2022 ). Similarly, studies indicated that lower body weight may significantly reduce the risk of diabetes and hypertension ( Amador et al, 2006 ; Pinto & Beltrán-Sánchez, 2015 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, older adults in this study with increased BMI had higher odds of being diagnosed with hypertension and diabetes. Consistent with the current findings, past research established that low body weight is an independent protective factor for hypertension ( Tang et al, 2022 ), whereas overweight/obesity are risk factors for hypertension and diabetes ( Chen et al, 2018 ; Medhi et al, 2021 ; Min & Cho, 2018 ; Tang et al, 2022 ). Similarly, studies indicated that lower body weight may significantly reduce the risk of diabetes and hypertension ( Amador et al, 2006 ; Pinto & Beltrán-Sánchez, 2015 ).…”
Section: Discussionsupporting
confidence: 91%
“…Another study showed that there is strong mediation effect of childhood insulin level with the childhood BMI status and that ultimately increases the risk of hypertension during adulthood and later life ( Zhang et al, 2016 ). It is also shown that the higher prevalence of hypertension and diabetes among those with overweight/obesity could be determined by dyslipidemia which is attributed to the elevated levels of cholesterol or fats (lipids) ( Tang et al, 2022 ). Therefore, the role of health risk behaviour, food intake, and other genetic factors needs to be explored further to better understand BMI classification and hypertension and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the prevalence is reported to be as high as 44.7% among adults aged 35–75 years ( 2 ). Hypertension is a multifactorial disease, with various influencing factors interacting with each other ( 3 ). Therefore, identification of risk factors for hypertension and effective early prevention are essential to lower the public health burden.…”
Section: Introductionmentioning
confidence: 99%
“…One hypertension study suggested that several additive interactions were found between the TyG index and certain anthropometric measures such as waist-to-height ratio and percentage of body fat only ( 33 ). Alternatively, Tang et al ( 42 ) demonstrated a potentiating effect modification between high BMI (e.g., overweight and obesity) and hypercholesteremia on hypertension. The observed interaction between BMI and hyperlipidemia can be potentially explained by an increased risk of developing metabolic syndrome and IR among overweight and obese people, which subsequently leads to the development of hypertension ( 43 ).…”
Section: Discussionmentioning
confidence: 99%